Ukrainian-Russian Border: from an Internal Administrative Border to an Inter-State One (Economic and Political Thought, 2014)
The existence of state borders is a condition for establishing the territoryof a state, the range of authority and the population that is subject to it. Thus,determining borderlines is an essential element of the establishment of statehood.Unfortunately, in case of Ukraine, that element has not been implemented,especially as far as the borderline with Russia is concerned. The first Ukrainiansovereign attempts to establish its eastern border failed when the Bolsheviksled their army on the march to Warsaw in June 1920. For the next 70 years,the almost 2,300 km long Ukrainian-Russian border remained an internaladministrative one. After 1991, then independent Ukraine started to make theeffort to be internationally recognised. The most important elements of that wereits bilateral agreements with Russia. At the turn of the century, the approval ofthe eastern Ukrainian border in the form of a treaty by the biggest neighbourwas finally achieved, however, its actual status was defective because of thelack of demarcation lines and a shortage of personnel, border infrastructure ormonitoring equipment. Problems with the protection of the Ukrainian-Russianborder to a large extent facilitated Russian aggression begun in March 2014. Inorder to understand the difficulties with separating the two countries, it is necessaryto take into account strong economic and social links between the societies onthe two sides of the border who used to live in one state for a few centuries.